2015
DOI: 10.1021/acs.est.5b03972
|View full text |Cite
|
Sign up to set email alerts
|

Alkali- and Sulfur-Resistant Tungsten-Based Catalysts for NOx Emissions Control

Abstract: The development of catalysts with simultaneous resistance to alkalis and sulfur poisoning is of great importance for efficiently controlling NOx emissions using the selective catalytic reduction of NOx with NH3 (SCR), because the conventional V2O5/WO3-TiO2 catalysts often suffer severe deactivation by alkalis. Here, we support V2O5 on a hexagonal WO3 (HWO) to develop a V2O5/HWO catalyst, which has exceptional resistance to alkali and sulfur poisoning in the SCR reactions. A 350 μmol g(-1) K(+) loading and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 37 publications
0
77
0
Order By: Relevance
“…As for commercial V 2 O 5 -WO 3 /TiO 2 , there was 73% removal efficient. The sulfur-poisoning of catalysts may be caused by the formation of thermally stable sulfate species, which deposited on catalysts’ surface and blocked catalytic sites [42,43]. However, after cutting off inlet SO 2 , the NO x conversion ratio of mesoporous WO 3 (1)-CeO 2 recovered to 93% after 3 h, and remained at 93%, showing that the mesoporous WO 3 (1)-CeO 2 had better reversible inhibition effect.…”
Section: Resultsmentioning
confidence: 99%
“…As for commercial V 2 O 5 -WO 3 /TiO 2 , there was 73% removal efficient. The sulfur-poisoning of catalysts may be caused by the formation of thermally stable sulfate species, which deposited on catalysts’ surface and blocked catalytic sites [42,43]. However, after cutting off inlet SO 2 , the NO x conversion ratio of mesoporous WO 3 (1)-CeO 2 recovered to 93% after 3 h, and remained at 93%, showing that the mesoporous WO 3 (1)-CeO 2 had better reversible inhibition effect.…”
Section: Resultsmentioning
confidence: 99%
“…developed Fe 1− x W x O δ catalysts with wide operating temperature windows by introducing W to Fe 2 O 3 . We recently reported that hexagonal WO 3 with abundant Brønsted acid sites had simultaneous resistance against SO 2 and alkalis in SCR ,. Therefore, hexagonal WO 3 should be an appealing support to make Fe 2 O 3 ‐based catalysts for real stack gas applications.…”
Section: Figurementioning
confidence: 99%
“…Finally, we used the stable alkali‐resistant V‐HMoO support for developing SCR catalysts by loading active V 2 O 5 on V‐HMoO ,. SCR experiments were conducted to investigate the resistance against alkali poisoning.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we recently established an ion exchange‐coordinate model as a guide for developing alkali‐resistant SCR catalysts . For instance, hexagonal WO 3 with strong acidity and abundant tunnels as the alkali‐trapping sites (ATSs) has been used as a support for loading V 2 O 5 ,. Another work reported by Chen et al.…”
Section: Introductionmentioning
confidence: 99%